Smartphone use by older adult in the healthy ageing process: a theory based on data - Adriana Martins Gallo; Juliane Pagliari Araujo; Wanessa Cristina Baccon; Francielle Renata Danielli Martins Marques; Maria Aparecida Salci; Lígia Carreira (Universidade de São Paulo, 2024)
Objective: to understand the feelings and recognitions of older adults when they experience the use of smartphones in everyday life, as well as the implications for the healthy aging process. Method: qualitative research, using the Unified Theory of Acceptance and Use of Technology; the Senior Technology Acceptance & Adoption Model and the methodological framework of Constructivist Grounded Theory. We intentionally recruited people aged 60+; smartphone users; participants for 6 months or more in an extension project, without cognitive impairment, determined by theoretical sampling. A semi-structured script guided data collection. Constant and concomitant comparative analysis followed the steps of initial and focused coding, supported by memos, until theoretical saturation. The Sankey diagram was used to analyze the data, using Atlas.ti software. Results: 37 participants were allocated to two sample groups. We present the category "Experiencing technological evolution during the aging process" and two subcategories: "Experiencing feelings when aging in the face of technological development"; "Using the smartphone and recognizing new experiences". Conclusion: when experiencing the use of smartphones, older adult understand and recognize the search for digital skills based on their need for usefulness and applicability of information and communication technology in their daily lives, integrating it into the healthy ageing process.